Inducing protein-protein interactions with molecular glues. Issue 15 (15th August 2018) - Che, Ye; Gilbert, Adam M.; Shanmugasundaram, Veerabahu; Noe, Mark C.
Graphical abstract: Highlights: Molecular glues promote the unnatural association of proteins to produce a therapeutic effect. Molecular glues alter the surface of proteins to promote their association. Natural products that promote protein interactions have inspired synthetic ligands with diverse pharmacology. Targeted protein association offers a new method for modulating cellular physiology and expands opportunity for drug discovery. Abstract: The drugable proteome is limited by the number of functional binding sites that can bind small molecules and respond with a therapeutic effect. Orthosteric and allosteric modulators of enzyme function or receptor signaling are well-established mechanisms of drug action. Drugs that perturb protein-protein interactions have only recently been launched. This approach is more difficult due to the extensive contact surfaces that must be perturbed antagonistically. Compounds that promote novel protein-protein interactions promise to dramatically expand opportunities for therapeutic intervention. This approach is precedented with natural products (rapamycin, FK506, sanglifehrin A), synthetic small molecules (thalidomide and IMiD derivatives) and indisulam analogues.